Android Based Hate Speech Search Applications Using TF-IDF Algorithm and Vector Space Models - R Dimas Adityo; Tri Yogi Rizqi; Mas Nurul Hamidah (Fakultas Teknik Universitas Bhayangkara, 2019)
The freedom in the use of social media becomes a common means in voicing opinions and expressions byissuing words or phrases of blasphemy (Hate Speech) in social media like Facebook. Hate speech and blasphemouswords are easily spread across social and general media not found that have transgressed the limits and can trace theunrest. To find out what the users of social media especially Facebook we have issued words or phrases of blasphemyon the basis of this report occurred. The study was conducted by using TF-IDF weighting algorithm and VSM (VectorSpace Model) calculation, while the data used was the 30 users post using Graph API. This research resulted in searchwith recall value: 2/2 = 1 which means the result of the relevant document and the precision value of the search resultis 2/13 = 0,154 which means result also raises irrelevant search result. Percentage of hate speech equivalence valuewas 43%.